The Influence of Contextual Learning Strategies on Student Learning Outcomes on Moral Creed Material at Mts Al-Muttaqien Balikpapan - Muhammad Yusuf Hilman; Iskandar Yusuf (Penerbit Hellow Pustaka, 2025)
This research aims to investigate the influence of contextual learning on student learning outcomes at MTs Al-Muttaqien Balikpapan. Considering that the choice of method in the education process is very influential, this research examines how the level of success of a method can influence student learning outcomes. The method used is associative quantitative research with linear regression analysis techniques. Data was obtained through distributing questionnaires filled in by 32 students, with instruments using a Likert scale. The normality test shows that the data is normally distributed, while the reliability test shows that the Cronbach's Alpha value is above 0.60, indicating the consistency of the measuring instrument. The results of linear regression analysis show that contextual learning has a significant positive effect on student learning outcomes, with an R Square value of 0.279. This means that 27.9% of the variation in student learning outcomes can be explained by contextual learning. The F test shows a sig value of 0.002 < 0.05, which indicates a significant relationship between the two variables. This research concludes that contextual learning can improve student learning outcomes significantly. It is recommended that schools pay attention to aspects of choosing learning methods to maximize student learning outcomes.